In silico and in vitro evaluation of antiviral activity of wogonin against main protease of porcine epidemic diarrhea virus - Wang, Jieru; Zeng, Xiaoyu; Yin, Dongdong; Yin, Lei; Shen, Xuehuai; Xu, Fazhi; Dai, Yin; Pan, Xiaocheng (Frontiers in Cellular and Infection Microbiology, 2023)
The high mortality rate of weaned piglets infected with porcine epidemic diarrhea virus (PEDV) poses a serious threat to the pig industry worldwide, demanding urgent research efforts related to developing effective antiviral drugs to prevent and treat PEDV infection. Small molecules can possibly prevent the spread of infection by targeting specific vital components of the pathogen’s genome. Main protease (Mpro, also named 3CL protease) plays essential roles in PEDV replication and has emerged as a promising target for the inhibition of PEDV. In this study, wogonin exhibited antiviral activity against a PEDV variant isolate, interacting with the PEDV particles and inhibiting the internalization, replication and release of PEDV. The molecular docking model indicated that wogonin was firmly embedded in the groove of the active pocket of Mpro. Furthermore, the interaction between wogonin and Mpro was validated in silico via microscale thermophoresis and surface plasmon resonance analyses. In addition, the results of a fluorescence resonance energy transfer (FRET) assay indicated that wogonin exerted an inhibitory effect on Mpro. These findings provide useful insights into the antiviral activities of wogonin, which could support future research into anti-PEDV drugs.`